An off-site construction readiness maturity model for the Indian construction sector. Issue 1 (6th October 2020) - Bendi, Deepthi; Rana, Muhammad Qasim; Arif, Mohammed; Goulding, Jack Steven; Sawhney, Anil
Abstract : Purpose: This paper aims to present an off-site construction (OSC) readiness maturity model for assessing the readiness of offsite construction companies in the Indian construction sector. Design/methodology/approach: The research was conducted in three stages. The first stage consisted of a detailed literature review to document 17 different variables affecting the OSC adoption in India. In Stage 2, 15 semi-structured interviews were carried out where the participants were asked to refine those variables for the Indian context and define what would be different levels of attainment. In the third stage, another set of 5 semi-structure interviews was performed to validate the maturity levels and definitions. Findings: A three-level OSC readiness maturity model is presented for discussion. This describes 17 variables at different levels of maturity. Practical Implications: The proposed OSC readiness maturity model guides construction practitioners in India through a structured process to enable them to assess their OSC readiness in the market. This assessment enables them to evaluate and benchmark their processes through the strategic and operational phases. The maturity model also identifies the areas of concern and the scope for further development or change to secure the optimal advantage of OSC methods. Originality/value: The research produced a model to assess the readiness of OSC adoption in the Indian construction sector. Although the model has been applied to the Indian construction sector, it can easily be modified to accommodate other OSM contexts.